Reconsidering Accounting Information Systems: Effective Formulations for Company’s Internal Control - Muhammad Fakhimuddin (Arthatama: Journal of Business Management and Accounting, 2018)
Every organization needs an accounting information system that has been planned and monitored properly to control the incoming and outgoing finances. By the accounting information system, organization is able to achieve the objectives of the organization. Internal control of a company is a process that is not easy to do. In controlling, a manager needs a lot of information from the company. Accounting information system is one way to obtain information needed in the control process. Internal control is also part of the evaluation carried out to control the implementation of company activities. The main purpose of internal control is to secure assets that are owned, examine the accuracy of accounting, managerial, and operational data. Internal control also aims to prevent accidental or unwanted things in the company. In the internal control process, decision making is also carried out. An information that has been reviewed by top management in the control process can be used as a reference in making policies or decisions.